Shaped by Confucius: The Cultural Origin of Corporate Behavior - Gu, Zhihui; Liang, Hao; Zhang, Hanyu (Journal of Financial and Quantitative Analysis, 2026)
Abstract We examine how Confucian culture operates as an informal institution by fostering relational contracts that substitute for formal legal frameworks in shaping corporate behavior. Using data on historical Confucian academies near firms’ headquarters in China, we find that greater cultural exposure is associated with higher investment in stakeholder relationships—measured by social contribution, stakeholder protection, courtesy expenses, patenting, and trade credit. These effects persist after controlling for human capital and alternative cultural influences, and weaken in regions with stronger formal institutions. Our findings highlight the enduring role of culture in supporting trust-based governance when formal contracting is limited.